Penerapan project based learning untuk meningkatkan hasil belajar mahasiswa pada matakuliah dasar-dasar sains - Fatikhatun Nikmatus Sholihah; Novia Ayu Pertiwi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
The low student learning outcomes and the use of information technology in the basics of science are caused by not applying the appropriate learning model. One effort to improve student learning outcomes is a project-based learning model. The purpose of this study is to improve student learning outcomes through the application of project-based learning. This study uses a one-group pretest-posttest design and this design that is doing a pretest before implementation and posttest after implementation. To find out the increase in student learning outcomes through project-based learning, the Wilcoxon test with SPSS was used. The results showed that student learning outcomes had increased from total pretest results less than 60 to higher than 80. Wilcoxon test results showed that the significance value was 0.001 < 0.05, meaning that there were differences in student learning outcomes from before the implementation and after the implementation of project-based learning. Based on the results of the research above, it can be concluded that the application through project-based learning can improve student learning outcomes in the basics of science.